Tasks to enhance the intercultural communicative competence of english language students with a second foreign language (french) at UCLV - Varela Spínola, Neusa Olinda (My University, 2012)
Nowadays Foreign Language Teaching entails greatly norms of social interaction in sociocultural communities and concerns to understand differences in interactional norms between sociocultural groups. Intercultural Communication Competence (ICC) is an important tool in this process which reinforces the teaching of skills and abilities to create a frame of mutually understood meanings across cultural boundaries. Therefore, the main goal of this diploma paper is to propose tasks to enhance ICC in the English Language Teaching at UCLV. In so doing, the diploma paper provides theoretical foundations of concepts related to the topic of research. Based on the theoretical framework and taking into account cross-cultural communication as point of departure, tasks are presented for teaching and improving Intercultural Communicative Competence at UCLV. The tasks proposed were evaluated using the assessment of specialists. Key Words Culture, Communicative Competence, Foreign Language Teaching, Intercultural Awareness, Intercultural Communication, Intercultural Communicative competence
Keywords: Literatura Inglesa/Estudio y Enseñanza; Foreign Language Teaching; Intercultural Communication Competence; English Language Teaching